2017
DOI: 10.30861/9781407315522
|View full text |Cite
|
Sign up to set email alerts
|

Early Microlithic Technologies and Behavioural Variability in Southern Africa and South Asia

Abstract: Early microlithic technologies and behavioural variability in southern Africa and South Asia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 197 publications
(454 reference statements)
1
19
0
Order By: Relevance
“…This is apparent in isolated assemblages such as Mehtakheri and Kana as well as better-resolved sequences at Patne and the Jurreru Valley. Indeed, casting the appearance of Late Paleolithic technology as a revolutionary change has served to downplay the importance of variability within Late Paleolithic assemblages, which recent studies are starting to shed light on (e.g., Lewis 2015;Lewis, Perera, and Petraglia 2014).…”
Section: The Middle To Late Paleolithic Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is apparent in isolated assemblages such as Mehtakheri and Kana as well as better-resolved sequences at Patne and the Jurreru Valley. Indeed, casting the appearance of Late Paleolithic technology as a revolutionary change has served to downplay the importance of variability within Late Paleolithic assemblages, which recent studies are starting to shed light on (e.g., Lewis 2015;Lewis, Perera, and Petraglia 2014).…”
Section: The Middle To Late Paleolithic Transitionmentioning
confidence: 99%
“…Typological comparisons between material culture in southern Africa and South Asia have been suggested to indicate direct cultural inheritance between these regions as a proxy for human dispersals (Mellars 2006;Mellars et al 2013). However, neither direct technological comparisons of lithic technologies (Lewis et al 2015) nor wider interregional syntheses (Groucutt et al 2015a(Groucutt et al , 2015b) support any form of cultural inheritance from MSA Howiesons Poort technologies in southern Africa or East African Later Stone Age industries with Late Paleolithic technologies in South Asia (contra Mellars 2006;Mellars et al 2013). A variant of such models advanced by Mishra and colleagues (Mishra, Chauhan, and Singhvi 2013) suggests that earlier human expansions may have colonized other regions in Asia but that modern human populations were unable to outcompete South Asian archaic populations.…”
Section: Explaining Cultural Developments In the Indian Subcontinentmentioning
confidence: 99%
“…Microlithic strategies are also not uniform in their technology. Recently, Lewis (2015) has documented how Late Pleistocene lithic miniaturization strategies in South Asia and southern Africa differed in terms of the the tools selected for retouch, core reduction techniques, and raw material selection. Her reanalysis of the microlithic Howieson"s Poort assemblages from Rose Cottage Cave and Umhlatuzana in South Africa has shown that geometric backed microliths, despite being the fossil directeur for the Howieson"s Poort, are a numerical inferior component of the small retouched tools at both sites (Lewis 2015).…”
Section: Table 1: Microlith Defintions and Sizesmentioning
confidence: 99%
“…Recently, Lewis (2015) has documented how Late Pleistocene lithic miniaturization strategies in South Asia and southern Africa differed in terms of the the tools selected for retouch, core reduction techniques, and raw material selection. Her reanalysis of the microlithic Howieson"s Poort assemblages from Rose Cottage Cave and Umhlatuzana in South Africa has shown that geometric backed microliths, despite being the fossil directeur for the Howieson"s Poort, are a numerical inferior component of the small retouched tools at both sites (Lewis 2015). Recent reanalysis of the Grey Sand layers at Sibudu Cave (63.8 ± 2.5 ka) has broadened its microlithic component to include the systematic production and use of small flakes and bladelets some of which were made using a bipolar technique (de la Peña and Wadley 2014).…”
Section: Table 1: Microlith Defintions and Sizesmentioning
confidence: 99%
See 1 more Smart Citation